Religious, Socio-Cultural, and Political Moderation in Pesantren Tegalsari, Ponorogo - Rofiq, Ahmad Choirul; Mujahidin, Anwar (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Pesantren Tegalsari (1700s-1964) contributed significantly to spreading Islam in Indonesia, especially in Ponorogo Regency, East Java. This study examined how Pesantren Tegalsari carried out religious, socio-cultural, and political moderation. This research used the historical method and theory of moderation. This research was conducted at the Pesantren Tegalsari in August 2023 by collecting data from observation at Tegalsari, in-depth interviews with the descendants of Kyai Ageng Muhammad Besari, and relevant references, such as Sejarah Kyai Ageng Mohammad Besari written by KH Moh. Poernomo, Babad Ponorogo written by Purwowijoyo, and other previous works on Pesantren Tegalsari. The analysis of moderation of Tegalsari Pesantren showed that Pesantren Tegalsari not only provided an example of implementing moderation in religious and socio-cultural aspects that prioritize tolerant behavior but also chose to be neutral in political conflict disputes on Java Island for the sustainability of education in Pesantren Tegalsari.